2017
DOI: 10.1097/ta.0000000000001372
|View full text |Cite
|
Sign up to set email alerts
|

Automated variable aortic control versus complete aortic occlusion in a swine model of hemorrhage

Abstract: Background Future endovascular hemorrhage control devices will require features that mitigate the adverse effects of vessel occlusion. Permissive regional hypoperfusion (PRH) with variable aortic control (VAC) is a novel strategy to minimize hemorrhage and reduce the ischemic burden of complete aortic occlusion (AO). The objective of this study was to compare PRH with VAC to AO in a lethal model of hemorrhage. Methods Twenty-five swine underwent cannulation of the supraceliac aorta, with diversion of aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…In the present case series, none of our patients had apparent reperfusion injury. A previous animal study described that calcium administration and insulin and glucose therapy were required for hyperkalemia secondary to reperfusion injury after prolonged REBOA use [ 28 ]. Therefore, we need to be cautious about reperfusion injury and blood tests, especially the serum potassium level, and arterial blood gas analysis should be performed frequently to find early evidence of reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case series, none of our patients had apparent reperfusion injury. A previous animal study described that calcium administration and insulin and glucose therapy were required for hyperkalemia secondary to reperfusion injury after prolonged REBOA use [ 28 ]. Therefore, we need to be cautious about reperfusion injury and blood tests, especially the serum potassium level, and arterial blood gas analysis should be performed frequently to find early evidence of reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in REBOA use for hemorrhage control, innovations to address certain key limitations have swiftly ensued. REBOA, while effective at controlling hemorrhage at bleeding points below the level of occlusion, is limited by the adverse effects of proximal aortic hypertension and progressive ischemic burden to distal tissue beds [1,2,5,7,13]. Therefore the technique of partially inflating a balloon catheter was proposed to slow bleeding and improve blood flow to the heart, lungs, and brain, while mitigating the ischemic insult below the balloon.…”
Section: Discussionmentioning
confidence: 99%
“…Our group's prior studies with robotic control systems have demonstrated that the precise regulation of ultra-low downstream aortic flow rates can balance the competing management priorities of hemostasis, blood pressure augmentation, and distal organ perfusion in the face of uncontrolled hemorrhagic shock [13][14][15]. This novel therapeutic concept, termed regionalized perfusion optimization (REPO), is predicated on a method that can precisely and dynamically control the flow of blood to the abdominal aorta, responding in real time to changing patient physiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 During EVAC, the balloon volume is precisely regulated to allow a small amount of blood flow to distal vascular beds to minimize ischemia and limit hemorrhage while still sustaining proximal arterial blood pressure. 4,5 Although prior studies 6 have demonstrated cardiovascular benefits along with reduced isotonic crystalloids requirements following simulated EVAC when compared to simulated complete REBOA, the mechanisms for these effects have not been elucidated. Here we propose to investigate endocrine responses as a possible contributor to simulated EVAC responses by analyzing frozen serum samples from a previous experiment.…”
Section: Introductionmentioning
confidence: 99%